Answer:520; 240
Step-by-step explanation:
a. 13, 26, 39, 52,......
a = First term = 13
d = common difference = 26 - 13 = 13
40th term = a + (n - 1)d = a + (40-1)d = a + 39d
= 13 + (39 × 13)
= 13 + 507
= 520
b. 6, 12, 18, 24,.......
a = First term = 6
d = common difference = 12 - 6 = 6
40th term = a + 39d
= 6 + 39(6)
= 6 + 234.
= 240
Answer:
f(x) = x⁴-6x³-13x²+66x+72
Step-by-step explanation:
Factors are: (x+3)(x+1)(x-4)(x-6)
[(x+3)(x+1)][(x-4)(x-6)]
[x²+3x+x+3][x²-4x-6x+24]
(x²+4x+3)(x²-10x+24)
x⁴+4x³+3x²-10x³-40x²-30x+24x²+96x+72
f(x) = x⁴-6x³-13x²+66x+72
That would of course be the third and only right answer
Step-by-step explanation:
BC is the bisector of
From equations (1) & (2)
(Because sides opposite to equal angles are equal)
Hence Proved